Yield and sward composition responses of a native grassland to compost application - Diaz, Daniel; Csízi, István (Acta Agraria Debreceniensis, 2017)
A major part of the animal products are based on the grasslands, due to the fact that the grassland ecosystems can be found all over the globe. In places where economical and successful crop production cannot be realized, the grassland based animal husbandry can be an efficient way of food production. In addition these ecosystems have an important role in carbon sequestration, and with their rich flora – and the fauna connected to it – in conservation of biodiversity. The protection of nature, and the sustainable agriculture is getting more and more attention in the European Union, but looking at the consumers’ needs, the production of healthy food cannot be neglected either. Because of these facts, the effects of two specific composts - which are officially authorized in organic farming, in Agri-environment Schemes and Natura 2000 programs – on grass yields and sward compositions were investigated in a field trial. The investigation took place in Hungary, on a natural grassland based on solonetz soil. The first type of compost was a natural one (N) without any additional material and the other one was enriched in phosphorus (E). Both was produced by the research institute, made of sheep manure. Three rates of compost (10 t ha-1, 20 t ha-1,30 t ha-1) were tested on 3 m×10 m experimental plots. Every treatments had four replications and both type of compost had four-four control plots too, this way 32 experimental plots were included in the investigations. The yield of the pasture was harvested two-times (in May and in September) and before cutting the plots measurements on botanical compositions were made. Samples for laboratory analysis were also taken. Dry matter yield and crude protein content was measured in laboratory and with the received data the yield per unit area was calculated. Based on the research results we can say that the application of compost in any dose inflicts higher dry material and crude protein yield. The changes were partly due to some positive changes in sward composition, because of the better nutrient conditions. The research results indicate, that use of organic compost can be an efficient way to increase grass yields in a sustainable way.